2019
DOI: 10.1007/s40279-019-01168-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sedentary Behaviour Reduction Workplace Interventions on Cardiometabolic Risk Markers: A Systematic Review

Abstract: Data Availability Statement All data generated or analysed for this review are included in this published article and its Electronic Supplementary Material documents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 100 publications
6
57
0
Order By: Relevance
“…Further, Gardner et al (2016) suggested that incorporating planning components into workplace sedentary interventions might be useful because occupational SB occurs in more predictable and structured contexts than leisure SB. These findings are also consistent with evidence that suggests that self‐regulatory strategies are promising behaviour change techniques to incorporate into sedentary interventions to reduce contextual barriers, decrease sitting time, and improve cardiometabolic risk (Brierley et al, 2019; Gardner et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Further, Gardner et al (2016) suggested that incorporating planning components into workplace sedentary interventions might be useful because occupational SB occurs in more predictable and structured contexts than leisure SB. These findings are also consistent with evidence that suggests that self‐regulatory strategies are promising behaviour change techniques to incorporate into sedentary interventions to reduce contextual barriers, decrease sitting time, and improve cardiometabolic risk (Brierley et al, 2019; Gardner et al, 2016).…”
Section: Discussionsupporting
confidence: 86%
“…Our findings may have important implications for health outcomes. It has been identified that workplace SB reduction interventions-especially those incorporating behaviour change techniques such as problem solving, goal setting, behavour substitution, and habit reversal-show promise for improving cardiometabolic risk markers (Brierley, Chater, Smith, & Bailey, 2019). A reduction in sitting time by 87 min/day, increases in time spent standing (+32.56 min/ day), walking (+14.33 min/day), and stretching (+11.34 min/day), as well as more frequent interruptions may result in positive health effects and, if sustained over time, could be associated with reduced risk of cardiovascular disease, type 2 diabetes, and all-cause mortality (Patterson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that intervening on sitting behaviors, for example, by reducing the time spent sitting or increasing sit-to-stand transitions, could be the first step toward a more active lifestyle [ 18 ]. Changing sedentary behavior by reducing the time spent sitting has yielded favorable changes in blood pressure, glucose control, insulin sensitivity, and waist circumference [ 19 ]. Data from randomized controlled trials (RCTs) are needed to determine if changes in sedentary time lead to health improvements in older adults outside of worksite settings.…”
Section: Introductionmentioning
confidence: 99%
“…Published SRs will also be searched to identify additional keywords. [14][15][16][17][18][19][20][21][22][23][24][25] In addition to these searches, we will search the reference lists of included publications to identify other relevant SRs. Field experts will be also be contacted, and searches on the Sedentary Behaviour Research Network website will be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulated evidence on the effects of such interventions has been discussed in several systematic reviews (SR). [14][15][16][17][18][19][20][21][22][23][24][25] The scope of these reviews largely varies according to whether included primary studies aim at specifically reducing SB, [14][15][16][17][18][19][20] increasing PA [21][22][23][24] or both. 25 Some SRs have focused on specific types of interventions, such as height-adjustable workstations 16 19 or cycle and treadmill desks 23 ; while others have focused on specific types of outcomes (eg, health outcomes 15 23 24 ) or populations (eg, women 24 ).…”
Section: What This Work Adds?mentioning
confidence: 99%